Effect of Heat Stress on Milk Production and Composition in Murrah Buffaloes - Pawar, Hitesh N.; Kumar, G.V.P.P.S. Ravi; Narang, Raman (Journal of Buffalo Science, 2013)
Temperature humidity index (THI) is widely used to assess the effect of temperature and relative humidity on performance in animals. In summer the THI was between 74 – 89 with average value of 81.18. in winter months THI ranged between 49 -70 with the average of 60. The results showed a significant effect of heat stress on daily milk yield and milk composition. In the present study the daily milk yield decreases from 4.46 to 3.65kg, heat stress reduced milk yield by 18.2%. There was a significant effect of heat stress on milk composition. Heat stress significantly reduced milk fat content from 8.3% during the winter to 7.19% during the summer. Milk protein percentage significantly decreased as a result of summer heat stress (3.08 vs.2.9 %, respectively for the winter and summer). In the present study the SNF decreases from 9.08 to 9.05 %, heat stress reduced SNF % as the THI value went from ≤ 74 to ≥ 83 in summer. Results showed that milk production is a function of THI. The negative slope of regression line indicates that milk production fat%, protein% and SNF% decreases as THI increases. This regression indicates that in general for each point increase in THI value. There was decrease in milk yield of 0.028kg per buffalo per day. Heat stress environments have been associated with depression in milk fat%, protein% and SNF%. There was decrease in milk fat of 0.046% per buffalo per day. There was also decrease in milk protein of 0.00014 % per buffalo per day. The decrease in milk SNF of 0.0047 % per buffalo per day.